Supramolecular Photoresponsive Systems - Ferrito, Maria Stefania <1986> (Alma Mater Studiorum - Università di Bologna, 2016)
This PhD research project deals with the synthesis and characterization of supramolecular photoresponsive systems based on the azobenzene unit. 1)Azobenzene-cyclodextrin inclusion complexes: the aim of this study was to obtain relatively simple, water-soluble derivatives, whose self-assembly could be reversibly controlled by light. On the basis of previous results, this opens the possibility of directly converting light into mechanical energy via osmosis. Several new azobenzene functionalized cyclodextrins have been synthesized, fully characterized and studied The inclusion complexes thus formed and their light-driven disassembly were studied by means of several complementary techniques including NMR, UV, CD, ICT, mass spectroscopy. The most suitable systems were used in experiments, still in progress, of light-to-mechanical energy conversion. 2)Azobenzene-guanosine hybrids: several novel azobenzene-guanosine hybrids were synthesized for the purpose of investigating the effect of cis-trans photoisomerization on guanosine self-assembly. Lipophilic guanosines in organic solvents can form either ribbon-like supramolecular polymers or, in the presence of alkali metal ions, G-quartet based supramolecular complexes. These complexes were fully characterized for newly synthesized azobenzene-guanosine hybrids. In the absence of ions, the ribbon-like supramolecular polymer gives rise to a gel-like system, which turned out to be a lyotropic liquid crystalline phase. Photoisomerization to cis form induces the transition to an isotropic solution, in a reversible fashion. In addition, the G-quartet structure obtained in the presence of alkali metal ions can be disassembled by light. 3) Oligoazobenzenes’s project. While several examples of electron-rich conjugated polymers are known and find application e.g. as electron donors in “plastic” photovoltaics, no examples are reported on the use of electron-poor conjugated polymers as acceptor counterpart. In particular, no polyazobenzenes having the (-C6H4-N=N-) repeat unit have ever been reported. Although no polymeric has been obtained yet, we succeeded in synthesizing several homologues up to a tetramer. The compounds were subjected to photophysical, photochemical and electrochemical characterization.